Legal Consequences Of Unilateral Termination Of Distribution Contract By Principal Company Against Distributor - Wahab, Abdul (Universitas Islam Malang, 2024)
Abstract : A valid agreement shall apply as law to the parties. The agreement is binding on the parties and cannot be revoked or cancelled unilaterally only. If you want to withdraw or cancel it, you must obtain the consent of the other party, so it is agreed again. However, if there are sufficient reasons according to the Law, the agreement may be withdrawn or canceled unilaterally. in Article 1338 paragraph (2) of the Civil Code. states that: